THE INNOVATIVE POLICY OPTIONS FOR COASTAL FISHERIES ECONOMIC DEVELOPMENT: A CASE OF KWANDANG BAY COASTAL ECOSYSTEM - Noel Taylor Moore (Center for Science and Technology Development Studies, Indonesian Institute of Sciences, 2017)
Socio-environmental problems, such as climate change, pollution and habitat destruction, present serious challenges for fisheries economic development. The integration of interventions or investments within a coastal marine ecosystem, a defined spatial area, is considered important in the economic development of local communities leading to the planned outcomes of livelihoods, food security and conservation The coastal marine ecosystem, is the provider of products and services to the local economy adjacent to the ecosystem where the benefit flows, within that area, are interconnected. The roles of science, technology and innovation (STI) are an integral part of these multi-dimensional interventions. Hence the need for an integrated approach for these interventions by government and/or through donor funded projects to enhance economic development of coastal communities. The policy framework proposed is therefore an STI perspective of the links between these intervention and investment options, based on a ‘fisheries economic development Hub’ (Hub) and discussed using the multi-level perspective (MLP). The policy innovation proposal suggests an implementation strategy of a pilot project and analyses the selection and implications of a potential Indonesian site for the application of the Hub. This paper aims to introduce the MLP into the framework of coastal community-based fisheries economic development. Key words: policy innovation. coastal marine ecosystem, fisheries economic development Hub, value chains, multi-level perspective (MLP)